Test-retest reliability of the irrational performance beliefs inventory - Turner, M. J.; Slater, M. J.; Dixon, J.; Miller, A. (European Journal of Sport Science, 2018)
The irrational performance beliefs inventory (iPBI) was developed to measure irrational beliefs within performance domains such as sport, academia, business, and the military. Past research indicates that the iPBI has good construct, concurrent, and predictive validity, but the test-retest reliability of the iPBI has not yet been examined. Therefore, in the present study the iPBI was administered to university sport and exercise students (n = 160) and academy soccer athletes (n = 75) at three-time points. Time point two occurred 7 days after time point one, and time point three occurred 21 days after time point two. In addition, social desirability was also measured. Repeated-measures MANCOVAs, intra-class coefficients, and Pearson`s (r) correlations demonstrate that the iPBI has good test-retest reliability, with iPBI scores remaining stable across the three-time points. Pearson`s correlation coefficients revealed no relationships between the iPBI and social desirability, indicating that the iPBI is not highly susceptible to response bias. The results are discussed with reference to the continued usage and development of the iPBI, and future research recommendations relating to the investigation of irrational performance beliefs are proposed.